Macroelement and Microelement Contents in Wild Edible Mushroom Species from the Southern Regions of China - Chen, X.H.; Zhou, H.B.; Qiu, G.Z. (Asian Journal of Chemistry, 2010)
Macroelement (P, Na, K, Ca, Mg) and microelement (Zn, Fe, Mn, Cd, Cr, Pb) contents in 8 different wild-growing edible mushroom species collected from the southern regions of China were determined by flame and graphite furnace atomic absorption spectrometry. All element concentrations were determined on a dry weight basis. The highest mean concentration of macroelements was found for K (22.2 g/kg), followed by P (5.15 g/kg), Ca (2.66 g/kg), Mg (1.23 g/kg) and Na (1.18 g/kg). The ranges of macroelement concentrations for K, P, Ca, Mg and Na were 11.6-34.2, 3.42-8.02, 0.85-3.83, 0.57-1.90 and 0.77-1.43 g/kg, respectively. The mean microelement concentrations, across all tested fungi, were in the following order: Fe > Zn > Mn > Cd > Pb > Cr. The ranges of microelement concentrations for Fe, Zn, Mn, Cd, Pb and Cr were 471.3-2906, 82.8-274.2, 21.3-283, 0.4-91.8, 2.0-10.8 and 0.2-4.6 mg/kg, respectively. Levels of heavy metals (Cd, Pb) in Russula vinosa, Russula virescens and Lyophyllum decastses can be considered as low when compared with European statutory limits. Therefore, the three wild mushrooms can be used in well-balanced diets due to their contents of functional minerals.